Kardiomiopati Dilatasi pada Pasien HIV-AIDS - Purwowiyoto, Sidhi Laksono (Jurnal Kedokteran YARSI, 2018)
The heart and great vessels are not the sites most frequently affected by opportunistic infections and neoplastic processes in patients with acquired immune deficiency syndrome (AIDS). HIV-related disease is now recognized as an important cause of dilated cardiomyopathy, with a prevalence of 8%–30%. Patients with HIV-infection and dilated cardiomyopathy have a much worse prognosis than those with idiopathic dilated cardiomyopathy. Cardiac involvement in HIV represents a pathophysiologic, diagnostic and therapeutic challenge for cardiologists. This review describes pathophysiology, diagnosis, treatment and prognosis of HIV- dilated cardiomyopathy.